2017
DOI: 10.1126/scisignal.aah6275
|View full text |Cite
|
Sign up to set email alerts
|

Discovering relationships between nuclear receptor signaling pathways, genes, and tissues in Transcriptomine

Abstract: We previously developed a web tool, Transcriptomine, to explore expression profiling data sets involving small-molecule or genetic manipulations of nuclear receptor signaling pathways. We describe advances in biocuration, query interface design, and data visualization that enhance the discovery of uncharacterized biology in these pathways using this tool. Transcriptomine currently contains about 45 million data points encompassing more than 2000 experiments in a reference library of nearly 550 data sets retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 128 publications
0
27
0
Order By: Relevance
“…The functional interactions between nuclear receptors (NRs) and cytokine genes were obtained from the literature-reported network and the Nuclear Receptor Signaling Atlas (NURSA) Transcriptomine resource (Becnel et al, 2017) on July 26, 2019 (Table S4).…”
Section: Nuclear Receptor Functional Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional interactions between nuclear receptors (NRs) and cytokine genes were obtained from the literature-reported network and the Nuclear Receptor Signaling Atlas (NURSA) Transcriptomine resource (Becnel et al, 2017) on July 26, 2019 (Table S4).…”
Section: Nuclear Receptor Functional Interactionsmentioning
confidence: 99%
“…Indeed, NRs have been shown to modulate the expression of key cytokines, such as Il17a (Hermann-Kleiter et al, 2012;Ivanov et al, 2006) and TNF (Jiang et al, 1998), in immune cell differentiation and autoimmune disorders. To determine whether NRs identified by eY1H assays potentially regulate their target cytokine genes, we searched for functional evidence for the eY1H PDIs in the literature and in expression profiling datasets from the Nuclear Receptor Signaling Atlas (NURSA) Transcriptomine database (Becnel et al, 2017). Notably, for 80 of the 248 PDIs, the NR has been found to functionally regulate its target cytokine gene ( Figure 3B and Table S4); however, in most cases, direct DNA binding had not been reported.…”
Section: Role Of Nuclear Receptors In Modulating the Expression Of Cymentioning
confidence: 99%
“…Similarly, the MetaSignature DataBase (59), which is based on multi-cohort transcriptome analysis of transcriptomic data from over 100 diseases, identifies "Respiratory Syncytial Virus", "Dengue", and "Meta-Virus" as top diseases with statistically significant and negative effect sizes with respect to RBM4. Furthermore, The Signaling Pathways Project (https://www.signalingpathways.org/index.jsf) lists the IFNg receptor family as a potent regulator of RBM4 expression (60). In our own previous work (32), we established that RBM4 is necessary for protein expression of ULBP1, an NKGD2 ligand that acts a signal for recognition of virally infected cells by NK cells.…”
Section: Discussionmentioning
confidence: 94%
“…Our data identified TRAF6 as a gene specifically down-regulated when HIF-1β, and its homologue in Drosophila melanogaster, Tango, are depleted. Analysis, using Ominer [40,41], of public datasets for ChIP-seq revealed that several transcription factors occupy genomic regions within the TRAF6 promoter, including Basic Helix-Loop-Helix ones such as HIFs. Furthermore, analysis of publicly released datasets for HIF-1β ChIP-seq identified a specific binding site in the promoter region of TRAF6 in T47D breast cancer cells [26].…”
Section: Discussionmentioning
confidence: 99%